Phytobacteriology and its changing scenario - THIND, B.S. (Indian Phytopathology, 2013)
Phytobacteriology is a subdiscipline of plant pathology, which deals with plant pathogenic bacteria and plant diseases caused by them. It is generally viewed in context of harmful interactions or losses caused by bacterial plant pathogens. However, in the last one and a half decade, the concept of phytobacteriology has changed. Now, besides harmful effects of plant pathogenic bacteria, it includes beneficial bacterialplant interactions such as N2 fixation, promotion of plant growth by rhizosphere, phyllosphere and soil-inhabiting bacteria and interactions between different bacterial species. According to Dumenyo et al. (2001), phytobacteriology deals with plant-associated bacteria and their interactions with each other and with their hosts. Some of the beneficial aspects of phytobacteriology are the use of Ti-plasmid of Agrobacterium tumefaciens in genetic engineering; production of xanthan gums, extracellular polysaccharides, restriction endonucleases and pectin-degrading enzymes by bacteria. The potential of Ti-plasmid of A. tumefaciens to move genetic material within different bacteria and from bacteria to plants have made it an important tool in plant genetic engineering and it is widely used for this purpose. The production of agrocin by an avirulent bacterium, A. radiobacter (strains K 84 and K 1026) and its role in controlling crown gall disease on commercial scale is well documented. At present, there are more than 16 commercial biocontrol products based on different bacteria, including A. radiobacter, which are used to control plant diseases caused by different pathogens.